TOLERANCE OF HIGH ALTITUDE ACCLIMATIZED RATS TO BLOOD LOSS AT SEA LEVEL - Pipat Cherdrungsi (2018)
After acclimatization to high altitude, the sea level haemorrhagic tolerance of rats was measured by determining the bleeding volume which resulted in death under anaesthesia following cannulation. For each animal this was recorded as a bleeding volume index (BVI), the total volume of blood lost per 100 g of body weight. The mean BVI of altitude acclimatized rats was greater than that for non‐acclimatized rats (P 〈 0·001), showing that chronic exposure to altitude enabled the animals to tolerate more severe blood loss. Evidence is presented which suggests that the increased haemorrhagic tolerance resulted, in part, from an increased initial blood volume and an increased ability for arterial blood pressure regulation during haemorrhage. © 1981 The Physiological Society